Mechanical and Dimensional Investigation of Additive Manufactured Multimaterial Parts - Königshofer, Markus; Stoiber, Martin; Unger, Ewald; Grasl, Christian; Moscato, Francesco (Frontiers in Physics, 2021)
Additive manufacturing machines, based on the multi-material jetting technology are widely used for 3D printing of sophisticated medical models, which are aimed to be used for preoperative planning and surgical training. Gaining knowledge of process-related influences on mechanical and dimensional properties of 3D printed parts makes up an essential basis for the design and manufacture of medical models. There are few studies on characterization of multi-material parts, and those are limited to tests that are not based on standardized methods. Within the scope of this work, mechanical and dimensional investigations were performed on multi-material parts that were printed using an Objet500 – Connex3 3D printer (Stratasys Ltd., Minnesota, USA). Amongst test methods listed in DIN EN ISO 17296-3, tensile tests were chosen for mechanical characterization. In the tensile tests, combinations of four different materials (Tango+, VeroClear, VeroPureWhite, MED610) were tested in three build orientations (XY, YX, ZX). To investigate the orientation-depended printing accuracy, the tensile specimens were further checked for their dimensional accuracy. Statistically significant variations in the mechanical properties were found between different orientation levels. In general, specimens printed in XY orientation show higher tensile strength than YX and ZX oriented specimens. The tensile moduli determined are in the range from 0.2 to 2500 MPa and compare well with the tensile moduli found in soft biological tissues. Dimensional deviations were found highest for the length of ZX-oriented tensile specimens. For this orientation level it could be observed that multi-material specimens, which contain higher percentage of the soft material Tango+ are characterized by higher shrinkage. For tensile specimens printed from the pure photopolymer Tango+ a shrinkage of 4.6% in length was determined. In summary, it was found that with multi-material jetting technology, the increased shrinkage and lower mechanical strength in the ZX direction must be considered in the design process.